ZAKAZ ODRZUCENIA POZWU Z POWODU NIEDOPUSZCZALNOŚCI DROGI SĄDOWEJ W SPRAWACH Z ZAKRESU PRAWA PRACY - Kapela, Ilona (Zeszyty Prawnicze, 2016)
Interdiction of Dismissal of an Action Due to Inadmissibility of Sueing or Prosecuting in Labour Law Cases Summary Interdiction of dismissal a suit due to inadmissibility of sueing or prosecuting in labour law cases is one of many distinctions between civil process and proceedings before the labour courts. The aforementioned distinction is treated marginally in the literature as it is rarely referred to, which may lead to the conviction that it is not very significant. However, after the careful analysis, it is possible to see its impact on the protection of legitimate interest of an employee. In article 199 of the civil procedure code a certain principle was expressed. It was however modified, indicating that the action shall not be dismissed in situations referred to in the aforementioned article, and shall be applicable to cases where an employee or an insured is a plaintiff. Its aim is to protect claims of an employee and an insured as well as it is a lex specialis norm in relation to the one expressed in article 199 paragraph 1 point 1 of civil procedure code. It is also an exception to the principle defined in article 201 of civil procedure code: “referring the case in terms of jurisdiction shall be limited only to the courts”. Referring the case to another body on the basis of the article 464 of civil procedure code due to inadmissibility of sueing or prosecuting instead of dismissal of an action is one of many conveniences that enables an employee to overcome particular obstacles connected with a process. Moreover it contributes to strengthen care of legitimate interest of an employee and enables to meet the deadline of turning to that body (article 463 paragraph 2 of civil procedure code).